Poly[diaqua-μ(4)-biphenyl-4,4′-dicarboxylato-magnesium(II)] - Liu, Hsin-Kuan (International Union of Crystallography, 2009)
The solvothermal reaction of magnesium nitrate with biphenyl-4,4′-dicarboxylic acid in N,N-dimethylformamide and water leads to the formation of crystals of the title complex, [Mg(C(14)H(8)O(4))(H(2)O)(2)](n). In the crystal structure, the Mg cations are coordinated by six O atoms from two water molecules and four symmetry-related biphenyl-4,4′-dicarboxylate anions within slightly distorted octahedra. The Mg cations are located on a center of inversion, the biphenyl-4,4′-dicarboxylate anions around a twofold rotation axis and the water molecule in a general position. The Mg cations are linked by the anions into a three-dimensional framework.